The Economics of tort law applied to Internet intermediaries : example of intellectual property - Lefort, Marine (École nationale supérieure des mines de Paris, 2015)
La responsabilité des intermédiaires d'Internet fait débat dans un univers numérique de plus en plus complexe. Les intermédiaires offrent des services en ligne. Ils créent ou facilitent des transactions entre des parties tierces (hébergement, e-commerce, fournisseurs d'accès…). A la fin des années 1990, un consensus s'est établi sur l'instauration d'une responsabilité limitée pour ces acteurs, dans le but de favoriser leur développement ainsi que celui d'Internet par des externalités croisées. Cependant, l'apparition régulière de nouveaux usages a induit des externalités négatives affectant certains agents économiques. La multiplication récente de décisions de jurisprudence parfois contradictoires, en particulier dans le domaine de la propriété intellectuelle, vient désormais remettre en cause cette exemption. Elle fait naître un risque juridique pour les intermédiaires d'Internet. Ces-derniers doivent alors prendre en compte ce nouveau contexte dans leurs modèles d'affaires. Notre recherche étudie les comportements spécifiques que la responsabilité des intermédiaires d'Internet engendre à travers l'exemple de la propriété intellectuelle. En premier lieu nous décrivons l'évolution historique de cette responsabilité. Nous développons ensuite un modèle théorique simple qui explore l'influence du risque légal dans un contexte de concurrence entre un intermédiaire et un ayant droit du copyright. Enfin nous étendons ce modèle de concurrence aux différents comportements de protection que peuvent choisir les intermédiaires.
Keywords: Competencia; Competition law; Concurrence; Economie du droit; Intellectual property; Intermédiaires d’Internet; Internet; Internet intermediaries; Law and Economics; Propriedade intelectual; Propriété intellectuelle

Equal treatment as a principle to guide the regulation of intangibly transferred content : a case study on e-books using the examples of copyright exhaustion, reduced rates of VAT and fixed book pricing - Linklater, Emma (European University Institute, 2015)
Using e-books as a case study, this thesis considers whether the principle of equal treatment could play a role in driving more consistent and rational regulation of markets where content is available in both tangible and intangible formats. At present, although the content is the same, these formats are often subject to different rules. This difference in treatment has opened up discussions about whether current legal frameworks should be amended and in these discussions actors with very different standpoints have consistently invoked the language of equality to justify their varied stances. However, in these discussions there is no clear elaboration of what equality means or how it can be used, leading to abstract debates and eventually to arbitrary decisions. The thesis attempts to fill this gap by building a framework based on outcome equality to decide if intangible book formats should be treated ‘like’ tangible ones. It uses the objective underlying the existing rule as the standard for establishing likeness or difference and advocates that functional equality, rather than formal equality, is desirable because this takes account of the differences in the functionalities between content formats: Intangibility impacts on the functioning of the rule in question (e.g. quantitatively increased ease of circulation and copying) and it is only if these impacts can be neutralized that functional equality can be achieved. The framework is applied to the case studies of copyright exhaustion, reduced rates of VAT and fixed book pricing. These have been chosen in recognition of the range of decision-making powers between the national and EU levels in this cultural sector. Overall, the analysis shows that rationality can be inserted by using equal treatment as a guide, but that consistency is more difficult to achieve given the interaction between national and EU influences in the book market.
Keywords: Copyright; Cultural policy; Electronic publishing; European Union countries; Intellectual property

Challenges of Transnational Trademark Law Practice: The Case of Nigerian Companies’ Brands in OAPI States - Nwabueze, Caroline (Revue générale de droit, 2015)
Nigeria industrial growth has turned the country into an indispensable economic support for its neighbours. Only for the case of Cameroon, Nigeria has been the leading supplier with respectively 22% and 17.8% of imports in 2011 and 2012 with trade amounting to 328 billion FCFA per annum. This results in part from Nigerian companies’ exportations in local markets. Nigerian trademarks related to cosmetics, furniture, electronics, and pharmaceutical goods abound in neighbouring countries. However, a strengthening of Nigerian companies in regional markets encompasses strategies to avoid infringing on the trademark rights. Such strategies should include the consideration of special trademarks features by different institutions of the intellectual property (IP) system in the relevant neighbour export markets. This is by the mere fact that the legal status of those goods, although physical property, relies mainly on the material law applicable, which is trademark in the present case. Because the principle of territoriality requires that trademark protection be sought in the place where the goods are sold—and trademark applications filed in each country in which protection is sought—, Nigerian companies planning to outsource some business activity in neighbour markets will seek compliance with trademarks norms applicable in the Organisation africaine de la propriété intellectuelle (OAPI) of which those countries—Benin, Cameroon, Chad, and Guinea—are part. The trade partnership between companies from a common law trademark background on one hand, and civil law intellectual property community on the other, inevitably raises some frictions and trademarks issues. This article analyses the trademark challenges arising from Nigerian companies’ business decision to enter OAPI markets and export goods and services. The article firstly underlines the issues to be taken into consideration, including registration and enforcement of the companies’ marks in OAPI. Then the paper simultaneously reviews the dissimilarities issues between the Nigerian Trademark Act and the OAPI Trademark System to which the Nigerian companies are confronted. If trademark protection makes it easier for an enterprise to access transnational markets, the establishment of a Trademark Community with neighbouring countries helps for sure national industries to establish partnerships with other firms for sustainable development in the areas such as production, marketing, distribution or delivery of goods and services. In light of the trademark harmonisation in the European Union internal market, the present paper concludes by recommending the creation of a Trademark Community in the West and Central African region between Nigeria and its neighbouring countries. La croissance industrielle du Nigeria a fait de ce pays un soutien économique indispensable pour ses voisins. Pour ne citer que l’exemple du Cameroun, le Nigeria en a été le principal fournisseur avec respectivement 22 % et 17,8 % des importations en 2011 et 2012 et des importations dont la valeur s’élève à 328 milliards fr. cfa par année. Ceci résulte en partie des exportations des compagnies nigérianes vers les marchés locaux. Les marques de commerce nigérianes dans le domaine des cosmétiques, des meubles et des produits électroniques et pharmaceutiques abondent dans les pays voisins. Cependant, le renforcement des compagnies nigérianes dans les marchés régionaux englobe des stratégies pour éviter d’enfreindre les droits de propriété industrielle et commerciale. Dans le cadre de ces stratégies, les différentes institutions qui régissent la propriété intellectuelle (PI) dans les marchés d’exportation des pays voisins pertinents devraient prendre en compte des caractéristiques particulières relatives aux marques de commerce. Ne serait-ce que du simple fait que le statut juridique de ces produits, bien qu’ils soient des biens physiques, repose principalement sur le droit substantiel applicable, le droit de la marque de commerce dans ce cas. Parce que le principe de territorialité nécessite que la protection de la marque de commerce soit demandée dans le territoire où les biens sont vendus, et que cette protection doit être demandée dans chaque pays individuellement, les compagnies nigérianes qui prévoient externaliser des activités commerciales dans des marchés voisins chercheront à se conformer aux normes en matière de marques de commerce qui sont applicables au sein de l’Organisation africaine de la propriété intellectuelle (OAPI), dont font partie le Bénin, le Cameroun, le Tchad et la Guinée. Le partenariat commercial entre des entreprises soulève inévitablement, et ce, tant du point de vue de la common law que celui du droit civil, des frictions et des problèmes lorsqu’il s’agit de marques de commerce. Le présent article analyse les défis relatifs aux marques de commerce découlant de la décision commerciale des entreprises nigérianes de faire leur entrée dans les marchés de l’OAPI et d’y exporter des biens et services. L’article souligne premièrement les problèmes qui doivent être pris en considération, dont l’inscription et la mise en application des marques des entreprises membres de l’OAPI. Ensuite, ce texte examine simultanément les problèmes résultant des différences entre la Nigerian Trademark Act et le système de marques de commerce de l’OAPI, système auquel les entreprises nigérianes sont confrontées. Si la protection des marques de commerce facilite l’accès aux marchés transnationaux pour les entreprises, la mise en place, avec les pays voisins, d’une communauté en matière de marques de commerce aide assurément les industries nationales à établir des partenariats avec d’autres entreprises dans le but d’assurer un développement durable dans des domaines tels que la production, la commercialisation, la distribution ou la livraison de biens et services. À la lumière de l’harmonisation des marques de commerce dans le marché intérieur de l’Union européenne, le présent article conclut en recommandant la création d’une communauté de marques de commerce dans la région de l’Afrique occidentale et centrale, et qui réunirait le Nigeria et ses pays voisins.
Keywords: Afrique occidentale; Commerce transnational; Communauté de marques de commerce; Community trademark; Compagnies nigérianes; Enforcement; Intellectual property; Marque déposée; Mise en oeuvre; Nigerian companies; OAPI; Principe de territorialité; Principle of territoriality; Propriedade intelectual; Propriété intellectuelle; Trademark practice; Transnational trade; Western Africa

The sui generis and intellectual property protection of expressions of folklore in Africa - Nwauche, Enyinna Sodienye (North-West University, 2015)
This thesis articulates an optimum framework for the protection of expressions of folklore in Africa using a number of African countries – South Africa, Kenya, Ghana and Nigeria as case studies. This thesis argues that the existing sui generis and intellectual property rights protection in African countries are grossly inadequate in protecting expressions of folklore in these countries. An optimum framework for the protection of expressions of folklore would constitute a combination of the positive and negative protective model elaborated and implemented through a human and people's rights framework that recognises that communities that produce expressions of folklore should own and control how their intellectual property is protected. While a positive protective model explores how intellectual property rights such as copyright, trademarks, designs and performances may protect expressions of folklore through the endowment of such rights on communities, negative protective models examine how state and national competent authorities protect expressions of folklore on behalf of communities. An optimum framework for the protection of expressions of folklore recognises that regional and international perspectives are critical for the protection of folklore in third party countries and expressions of folklore that occur in contiguous countries. A regional perspective is important for Africa countries because of two regional intellectual property organisations in Africa (ARIPO – African Regional Intellectual Property Organisation) and OAPI (African Intellectual Property Organisation) that have established minimum standards for the protection of expressions of folklore. Norm setting and standards in international organisations such as WIPO (World Intellectual Property Organisation); UNESCO (United Nations Educational Cultural and Scientific Organisation); and the WTO (World Trade Organisation) significantly impact the protection of expressions of folklore in Africa. A human and peoples' rights framework explores how national and regional legal systems in Africa recognise entitlements of communities in the protection of the expressions of folklore they produce. In this regard, the normative framework of communities in terms of their customary law is also explored.
Keywords: ARIPO; African Regional Intellectual Property Organization; Communities; Customary law; Expressions of folklore; Ghana; Indigenous people; Intellectual property; Intellectual property rights; Kenya; Nigeria; Peoples' rights; South Africa; Sui generis; WIPO; World Intellectual Property Organization